Business Planning for Men's Big Size Fashion: A Case of BIG SIZE BRO in Bandung - Supriatna, Supriatna; Kaniawati, Keni (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Industry in Indonesia is experiencing significant growth over the last few decades, however, there are still untapped market segments that have not been optimally developed, one of which is big-sized fashion for men. This Research aims to compile planning for BIG SIZE BRO, a big men's fashion business in Bandung City. With the use of the Business Model Canvas (BMC) method, study the financial eligibility, SWOT analysis, research, and presentation planning strategies for an integrated business. The result shows that the market opportunity for men's big size fashion in Bandung is quite large. Big, with potential growth supported by social media trends, preferences of consumers, and the lack of local brand dominance in this segment. This study can become a guide for candidate entrepreneurs in designing competitive and sustainable businesses in the men's fashion sector